Development of chitosan 2D film scaffolds and nanoparticles enriched with royal jelly and grape seed extract: Enhanced antibacterial and wound healing activity - Marei, Narguess (AUC Knowledge Fountain, 2019)
Wound healing using nanomaterials have been increasingly studied due to their remarkable applicability in tissue engineering. Biopolymeric scaffolds have been widely used to fabricate wound dressings and skin substitute. Chitosan the deacetylated form of chitin has received great attention especially in wound healing. Natural extracts such as garlic, curcumin, honey, royal jelly and grape seed extract were used to enhance the fabricated wound dressing materials. In this work, Vitis vinifera (Grape seed extract) and royal jelly were loaded within fabricated low and high molecular weight chitosan 2D film scaffolds and nanoparticles. Vitis vinifera was known with its dermal wound healing properties as well as its antioxidant activity. Royal jelly has been demonstrated to possess in vitro and in vivo antimicrobial, anti-inflammatory and wound healing capabilities in experimental animals. Scaffolds were physicochemically characterized using Fourier transform infrared spectroscopy (FTIR), and X ray diffraction (XRD). Scaffolds morphology was visualized using scanning electron microscope (SEM). Particle size distribution and zeta potential for the chitosan nanoparticles were predicted. In vitro antibacterial testing of the prepared scaffolds and nanoparticles was performed against Bacillus subtilis, Staphylococcus aureus, Enterobacter aerogenes, and Pseudomonas aeruginosa. In addition, the prepared scaffolds and nanoparticles showed no cytotoxicity for human lung fibroblast (Wi38). A preliminary in vivo study revealed that the developed scaffolds and nanoparticles enhanced the wound healing process as compared to the untreated control rat wound closure rate.